First detection of Cyprinid Herpesvirus 2 (CyHV‐2) in goldfish (Carassius auratus) in France. Issue 6 (14th July 2015) - Boitard, P‐M; Baud, M; Labrut, S; de Boisséson, C; Jamin, M; Bigarré, L
Abstract: Massive mortalities of Carassius auratus (L.) occurred in a farm in France during summer 2014. Fish presented anorexia, loss of scales and large amounts of mucus on the gills. Necrosis of the distal tip of the filament and the lamellae, combined with fusion of the lamellae, was observed, as well as necrosis in the hematopoietic organs and in the digestive tract. The histological examination led to hypothesize the implication of a virus in the mortality. The presence of cyprinid herpesvirus 2 (CyHV‐2) in dead fish was demonstrated by amplification and sequencing of portions of the DNA polymerase and helicase genes, both sequences exhibiting 100% identity with CyHV‐2 from Japan. In an attempt to find genetic markers of variation, two regions containing tandem repeats in the Japanese genome were amplified from a virus‐positive sample from the present outbreak. A first region (mB) was fully identical to the Japanese isolate. However, the second region (mA) exhibited a range of deletions and substitutions compared to CyHV‐2 from Japan. This is the first report of CyHV‐2 in France in association with mortality of goldfish and the first identification of a molecular marker for its tracing.